The impact of political ideologies on cultural erosion: Indigenous education policy in Brazil (2009–2022) - André Calixto Gonçalves; Rodolfo Valentim; Francisco Aparecido Rodrigues; Guilherme Antônio de Almeida Lopes Fernandes; Ivan Filipe Fernandes (PLoS ONE, 2026)
Indigenous schools in Brazil aim to provide equitable education to both Indigenous and non-Indigenous communities. As of 2022, there were 3,411 such schools operating nationwide, serving the entire Indigenous population. However, an analysis of educational data reveals significant non-compliance with legislation designed to integrate Indigenous culture into the curriculum. Our research demonstrates that the school system frequently falls short of its legal obligation to promote and safeguard Indigenous cultural values. The systematic suppression of culturally specific materials and native languages is particularly alarming and appears to be associated with the influence of far-right political administrations. This study analyzes school census data from 2009 to 2022, employing chi-square tests, Cramer’s V tests, descriptive statistics and for robustness hierarchical mixed models to examine the relationship between political ideology and educational practices.